Crosslinked oxidized sodium hyaluronate as well as preparation method and application thereof
By controlling the molecular weight and oxidation degree of sodium hyaluronate and cross-linking reaction with amino acids and trehalose, cross-linking sodium hyaluronate with high support and stability was prepared, which solved the problem of unstable structure of cross-linked sodium hyaluronate in the prior art, and significantly improved its anti-inflammatory and wound healing effect.
Patent Information
- Application Number
- CN202411840076.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-28
AI Technical Summary
The prior art is difficult to control the molecular weight, molecular weight distribution, oxidation degree and crosslinking degree of sodium hyaluronate, resulting in the inability to form a three-dimensional network structure with high support, affecting its anti-inflammatory and wound healing effect.
By controlling the molecular weight, molecular weight distribution and oxidation degree of oxidized sodium hyaluronate, and cross-linking reaction with amino acids and trehalose after activation using sodium citrate, cross-linking sodium hyaluronate with high elasticity and high stability was prepared.
The high support, stability and elasticity of cross-linked oxidized sodium hyaluronate is achieved, which significantly improves its wound healing, anti-inflammatory and antioxidant effects in medicine and cosmetics.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the field of medical technology, and specifically relates to a cross-linked oxidized sodium hyaluronate and a preparation method and application thereof. Background Art
[0002] Hyaluronic acid is a linear polysaccharide polymer composed of disaccharide repeating structural units connected by β-(1-3) glycosidic bonds between D-glucuronic acid and N-acetyl-D-glucosamine. Since the polysaccharide chain carries a large number of carboxyl and amino groups, it has a large negative charge, which can attract water, so that the polysaccharide molecules form a colloidal solution in water; the carboxyl and amino groups on the polysaccharide chain can also interact with other molecules, thereby affecting their physiological functions. Sodium hyaluronate can be directly injected into the joint cavity as a lubricant for the treatment of arthritis. Moisturizing Sodium hyaluronate's moisturizing effect in skin tissue is one of its most important physiological functions. Adequate moisture makes the skin smooth and delicate. Sodium hyaluronate also has anti-wrinkle, anti-oxidation, thickening, film-forming, and wound healing effects.
[0003] Chinese invention patent CN114404355A discloses a sodium hyaluronate gel and its preparation method and application. The preparation method of sodium hyaluronate gel in the invention comprises the following steps: preparing a sodium hyaluronate solution at room temperature; adding a cross-linking agent to the sodium hyaluronate solution, stirring and mixing, and slowly adding a sodium hydroxide ethanol solution to prepare a reaction solution; heating the reaction solution to 35-55°C, cross-linking at a constant temperature for 3-8 hours, adjusting the pH of the solution after the reaction to neutral with dilute hydrochloric acid, filtering and removing the filtrate, and vacuum drying to obtain a filter cake; mixing the filter cake with a phosphate buffer solution with a pH of 7.2, stirring, washing, filtering, adding lidocaine hydrochloride, stirring and dissolving, and preparing a sodium hyaluronate gel. The invention uses an ethanol solution containing sodium hydroxide for alcohol precipitation, which can greatly shorten the contact time between sodium hyaluronate and alkali, and effectively reduce the breakage of the sodium hyaluronate molecular chain and the decomposition of acetylamino. And then improve skin problems such as dryness, fine lines, and dullness.
[0004] Chinese invention patent CN111228579A discloses an injectable hydrogel and its preparation method and application as well as a joint lubricant; the injectable hydrogel comprises the following raw materials: a macromolecular biocrosslinker, a small molecule crosslinker and carboxymethyl chitosan; the macromolecular biocrosslinker comprises at least one of oxidized sodium hyaluronate, oxidized sodium alginate, oxidized sodium carboxymethyl cellulose, oxidized starch and oxidized dextran, and the oxidation degree of the macromolecular biocrosslinker is 10%-80%; the small molecule crosslinker comprises an aldehyde crosslinker with a molecular weight of less than 200Da. The injectable hydrogel has a good effect on cartilage lubrication protection in the treatment of osteoarthritis, and can play a role in prolonging the treatment effect and reducing the number of administrations.
[0005] Chinese invention patent CN112007202A discloses an adhesive healing-promoting hemostatic sponge, which is made of 1.5%-3.5% by weight of dopamine-grafted oxidized sodium hyaluronate, 0.5%-1.0% exosomes, 15%-25% acrylic acid and 0.01%-0.02% N,N'-methylenebisacrylamide, neutralized with an alkaline neutralizer, and then added with a redox initiator to initiate cross-linking, and then freeze-dried and sterilized. The molecular weight of the dopamine-grafted oxidized sodium hyaluronate is 8KDa-80KDa, the degree of oxidation is 40%-60%, and the dopamine grafting rate is 5%-10%.
[0006] Although sodium hyaluronate is widely used in the fields of medicine, medical machinery, cosmetics, etc., the molecular weight, molecular weight distribution, oxidation degree, etc. of sodium hyaluronate have a great influence on the performance of the cross-linked material; if the method for preparing cross-linked sodium hyaluronate is inappropriate, a cross-linked sodium hyaluronate with a three-dimensional network structure with support cannot be formed, which affects its anti-inflammatory and wound healing ability. Therefore, it is necessary to provide a cross-linked oxidized sodium hyaluronate and a preparation method thereof, and control the molecular weight and molecular weight distribution, oxidation degree and cross-linking degree of sodium hyaluronate to obtain a cross-linked sodium hyaluronate with a suitable viscosity, high stability and a three-dimensional network structure with high support. Summary of the invention
[0007] In view of the problems existing in the prior art, the present invention provides a cross-linked oxidized sodium hyaluronate and a preparation method and application thereof. By controlling the molecular weight, molecular weight distribution and oxidation degree of the raw material sodium hyaluronate, sodium citrate is used to activate the sodium hyaluronate, and amino acids and trehalose are used to perform cross-linking under the condition of an activator to obtain cross-linked oxidized sodium hyaluronate with high elasticity and high stability, which is used in the preparation of medicines and cosmetics with significant effects of promoting wound healing and high antioxidant and anti-inflammatory effects.
[0008] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0009] First, the present invention provides a method for preparing cross-linked oxidized sodium hyaluronate, comprising the steps of:
[0010] (1) mixing oxidized sodium hyaluronate with water, adding sodium citrate to adjust the pH to 7.0-8.0, and obtaining a treated oxidized sodium hyaluronate aqueous solution; the oxidized sodium hyaluronate has an oxidation degree of 10%-90% and a weight average molecular weight of 5 kDa-200 kDa;
[0011] (2) mixing the oxidized sodium hyaluronate aqueous solution treated in step (1) with an activator to obtain an activated oxidized sodium hyaluronate aqueous solution; the activator is a mixture of adipic acid dihydrazide (ADH) and carbodiimide (EDC, N-(3-dimethylaminopropyl)-N-ethylcarbodiimide);
[0012] (3) cross-linking the activated oxidized sodium hyaluronate aqueous solution in step (2) with amino acids and trehalose to obtain cross-linked oxidized sodium hyaluronate;
[0013] The amino acid is selected from at least one of histidine, arginine, ε-polylysine or its hydrochloride, glutamine and asparagine.
[0014] Preferably, in step (1), the degree of oxidation of the oxidized sodium hyaluronate is 20%-75%.
[0015] Further preferably, in step (1), the degree of oxidation of the oxidized sodium hyaluronate is 20%-50%.
[0016] More preferably, in step (1), the degree of oxidation of the oxidized sodium hyaluronate is 25%-45%.
[0017] More preferably, in step (1), the degree of oxidation of the oxidized sodium hyaluronate is 33%-40%.
[0018] Preferably, in step (1), the weight average molecular weight of the oxidized sodium hyaluronate is 10 kDa-100 kDa.
[0019] Further preferably, in step (1), the weight average molecular weight of the oxidized sodium hyaluronate is 10 kDa-50 kDa.
[0020] More preferably, in step (1), the weight average molecular weight of the oxidized sodium hyaluronate is 25 kDa-50 kDa.
[0021] More preferably, in step (1), the weight average molecular weight of the oxidized sodium hyaluronate is 30 kDa-45 kDa.
[0022] More preferably, in step (1), the weight average molecular weight of the oxidized sodium hyaluronate is 36 kDa-41 kDa.
[0023] Preferably, in step (1), the solid-to-liquid ratio of the oxidized sodium hyaluronate to water is 1:250-400 g / mL.
[0024] Further preferably, in step (1), the solid-liquid ratio of the oxidized sodium hyaluronate to water is 1:300 g / mL.
[0025] Preferably, in step (1), the pH is 7.2-7.6; further preferably, the pH is 7.5.
[0026] Preferably, in step (2), the molar ratio of ADH to EDC is 1:3-5.
[0027] Further preferably, in step (2), the molar ratio of ADH to EDC is 1:3-4.
[0028] More preferably, in step (2), the molar ratio of ADH to EDC is 1:4.
[0029] Preferably, in step (2), the mass ratio of the oxidized sodium hyaluronate to the activator is 1:0.3-0.6.
[0030] Further preferably, in step (2), the mass ratio of the oxidized sodium hyaluronate to the activator is 1:0.5.
[0031] Preferably, in step (2), the mixing reaction time is 0.5-3h.
[0032] Further preferably, in step (2), the mixing reaction time is 1-2 hours.
[0033] Preferably, in step (3), the amino acid is selected from at least one of histidine, arginine, ε-polylysine or their hydrochlorides.
[0034] Preferably, in step (3), the mass ratio of the oxidized sodium hyaluronate to the amino acid is 1:0.1-1.
[0035] Further preferably, in step (3), the mass ratio of the oxidized sodium hyaluronate to the amino acid is 1:0.2-0.6.
[0036] More preferably, in step (3), the mass ratio of the oxidized sodium hyaluronate to the amino acid is 1:0.3-0.4.
[0037] Preferably, in step (3), the mass ratio of the oxidized sodium hyaluronate to trehalose is 1:0.05-0.5.
[0038] Further preferably, in step (3), the mass ratio of the oxidized sodium hyaluronate to trehalose is 1:0.1-0.3.
[0039] More preferably, in step (3), the mass ratio of the oxidized sodium hyaluronate to trehalose is 1:0.2.
[0040] Preferably, in step (3), the reaction time is 4-12 h; further preferably, the reaction time is 6-10 h; further preferably, in step (3), the reaction time is 8 h.
[0041] During the reaction process of step (1) to step (3) of the present invention, stirring is required.
[0042] In the present invention, unless otherwise specified, the reaction temperature is room temperature.
[0043] In the present invention, the carboxyl groups in the oxidized sodium hyaluronate are first activated, and sodium citrate also has a certain protective effect on the hydroxyl group; then, the treated oxidized hyaluronic acid solution is reacted with an activator, and the adduct generated by the carboxyl group and the activator reacts with a cross-linking agent (amino acid, small molecule aldehyde compound), and the cross-linking agent attacks the adduct as a nucleophilic group to form a cross-linking agent without an activator. The obtained cross-linked oxidized sodium hyaluronate has a high degree of cross-linking, stable cross-linking properties, stable elasticity, and strong supporting force.
[0044] Then, the present invention provides a cross-linked oxidized sodium hyaluronate prepared by the above preparation method.
[0045] Preferably, the cross-linked oxidized sodium hyaluronate is prepared from raw materials including: oxidized sodium hyaluronate, sodium citrate, adipic acid dihydrazide, carbodiimide, amino acids and trehalose.
[0046] More preferably, the oxidation degree of the oxidized sodium hyaluronate is 10%-90%.
[0047] More preferably, the oxidation degree of the oxidized sodium hyaluronate is 20%-75%.
[0048] More preferably, the oxidation degree of the oxidized sodium hyaluronate is 20%-50%.
[0049] More preferably, the oxidation degree of the oxidized sodium hyaluronate is 25%-45%.
[0050] More preferably, the oxidation degree of the oxidized sodium hyaluronate is 33%-40%.
[0051] More preferably, the weight average molecular weight of the oxidized sodium hyaluronate is 5 kDa-200 kDa.
[0052] More preferably, the weight average molecular weight of the oxidized sodium hyaluronate is 10 kDa-100 kDa.
[0053] More preferably, the weight average molecular weight of the oxidized sodium hyaluronate is 10 kDa-50 kDa.
[0054] More preferably, the weight average molecular weight of the oxidized sodium hyaluronate is 25 kDa-50 kDa.
[0055] More preferably, the weight average molecular weight of the oxidized sodium hyaluronate is 30 kDa-45 kDa.
[0056] More preferably, the weight average molecular weight of the oxidized sodium hyaluronate is 36 kDa-41 kDa.
[0057] More preferably, the molar ratio of adipic acid dihydrazide to carbodiimide is 1:3-5.
[0058] More preferably, the molar ratio of adipic acid dihydrazide to carbodiimide is 1:4.
[0059] Further preferably, the mass ratio of the oxidized sodium hyaluronate to the activator is 1:0.3-0.6.
[0060] More preferably, the mass ratio of the oxidized sodium hyaluronate to the activator is 1:0.5.
[0061] More preferably, the amino acid is selected from at least one of histidine, arginine, ε-polylysine or its hydrochloride, glutamine and asparagine.
[0062] Further preferably, the mass ratio of the oxidized sodium hyaluronate to the amino acid is 1:0.1-1.
[0063] More preferably, the mass ratio of the oxidized sodium hyaluronate to the amino acid is 1:0.2-0.6.
[0064] More preferably, the mass ratio of the oxidized sodium hyaluronate to the amino acid is 1:0.3-0.4.
[0065] Further preferably, the mass ratio of the oxidized sodium hyaluronate to trehalose is 1:0.05-0.5.
[0066] More preferably, the mass ratio of the oxidized sodium hyaluronate to trehalose is 1:0.1-0.3.
[0067] More preferably, the mass ratio of the oxidized sodium hyaluronate to trehalose is 1:0.2.
[0068] Finally, the present invention provides the use of the cross-linked oxidized sodium hyaluronate in the preparation of medicines and / or cosmetics with high stability, wound healing promotion, anti-inflammatory and antioxidant effects.
[0069] Further preferably, the dosage form of the medical drug in the application is not limited to dressing.
[0070] Compared with the prior art, the present invention has the following beneficial effects:
[0071] 1. The present invention uses sodium citrate to activate sodium hyaluronate. At the same time, sodium citrate also acts as an auxiliary protective agent for hydroxyl groups to further improve the cross-linking strength, so that the cross-linked oxidized sodium hyaluronate forms a three-dimensional network structure with high support force, thereby significantly improving elasticity and stability.
[0072] 2. The present invention uses oxidized sodium hyaluronate with a specific molecular weight, molecular weight distribution and oxidation degree to carry out a cross-linking reaction with a cross-linking agent and trehalose, and increases the cross-linking strength by controlling the types of the cross-linking agent and the activator, thereby increasing the viscosity of the cross-linked oxidized sodium hyaluronate, maintaining the viscosity within a range with a relatively high supporting force, and increasing the wound healing speed when acting on the wound.
[0073] 3. The present invention applies cross-linked oxidized sodium hyaluronate to drug preparation. Due to its high supporting strength and appropriate viscosity, it has the effect of significantly promoting wound healing, shortening wound healing time, reducing inflammatory response and preventing the formation of scars. DETAILED DESCRIPTION
[0074] The following non-limiting examples can enable those skilled in the art to more fully understand the present invention, but do not limit the present invention in any way. The following content is merely an exemplary description of the scope of the present invention, and those skilled in the art can make various changes and modifications to the present invention based on the disclosed content, which should also fall within the scope of the present invention.
[0075] When the embodiments give numerical ranges, it should be understood that, unless otherwise specified in the present invention, both endpoints of each numerical range and any numerical value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used in the present invention have the same meanings as those generally understood by those of ordinary skill in the art to which the present invention belongs.
[0076] The present invention is further described below by way of specific examples. Unless otherwise specified, the various chemical reagents used in the examples of the present invention are obtained through conventional commercial channels.
[0077] In the present invention, the carbodiimide used is N-(3-dimethylaminopropyl)-N-ethylcarbodiimide hydrochloride; the activators of the present invention are all purchased from Sigma. The trehalose of the present invention is D-trehalose. Products from different manufacturers have no significant effect on the effect.
[0078] Example 1
[0079] A cross-linked oxidized sodium hyaluronate, the preparation method of which is as follows:
[0080] (1) mixing oxidized sodium hyaluronate having an oxidation degree of 40% and a weight average molecular weight of about 36.8 kDa with water, wherein the solid-liquid ratio of oxidized sodium hyaluronate to water is 1:300 g / mL; adding sodium citrate, adjusting the pH of the aqueous solution to 7.5, and stirring uniformly to obtain a treated oxidized sodium hyaluronate aqueous solution;
[0081] (2) mixing an aqueous solution of oxidized sodium hyaluronate with an activator in a mass ratio of 1:0.5, stirring and reacting for 2 hours to obtain an activated aqueous solution of oxidized sodium hyaluronate; the activator is N-(3-dimethylaminopropyl)-N-ethylcarbodiimide hydrochloride and adipic acid dihydrazide in a molar ratio of 1:4;
[0082] (3) The activated oxidized sodium hyaluronate aqueous solution was stirred and mixed with histidine and trehalose for 8 hours to obtain cross-linked oxidized sodium hyaluronate; the mass ratio of the oxidized sodium hyaluronate to histidine was 1:0.4, and the mass ratio of the oxidized sodium hyaluronate to trehalose was 1:0.2.
[0083] Example 2
[0084] Different from Example 1, the weight average molecular weight of the oxidized sodium hyaluronate raw material is 36.8 kDa.
[0085] The rest is the same as in Example 1.
[0086] Example 3
[0087] Different from Example 1, the weight average molecular weight of the oxidized sodium hyaluronate raw material is 40.8 kDa.
[0088] The rest is the same as in Example 1.
[0089] Example 4
[0090] A cross-linked oxidized sodium hyaluronate, the preparation method of which is as follows:
[0091] (1) mixing oxidized sodium hyaluronate having an oxidation degree of 33% and a weight average molecular weight of about 25 kDa with water, wherein the solid-to-liquid ratio of oxidized sodium hyaluronate to water is 1:250 g / mL; adding sodium citrate, adjusting the pH of the aqueous solution to 7.2, and stirring uniformly to obtain a treated oxidized sodium hyaluronate aqueous solution;
[0092] (2) mixing the treated oxidized sodium hyaluronate aqueous solution with an activator, wherein the mass ratio of oxidized sodium hyaluronate to activator is 1:0.3, and mixing and stirring for 1 hour to obtain an activated oxidized sodium hyaluronate aqueous solution; the activator is N-(3-dimethylaminopropyl)-N-ethylcarbodiimide hydrochloride and adipic acid dihydrazide in a molar ratio of 1:4;
[0093] (3) The activated oxidized sodium hyaluronate aqueous solution is stirred and mixed with glutamine and trehalose for 10 hours to obtain cross-linked oxidized sodium hyaluronate; the mass ratio of the oxidized sodium hyaluronate to glutamine is 1:0.3, and the mass ratio of the oxidized sodium hyaluronate to trehalose is 1:0.3.
[0094] Example 5
[0095] A cross-linked oxidized sodium hyaluronate, the preparation method of which is as follows:
[0096] (1) mixing oxidized sodium hyaluronate having an oxidation degree of 50% and a weight average molecular weight of about 50 kDa with water, wherein the solid-liquid ratio of oxidized sodium hyaluronate to water is 1:400 g / mL; adding sodium citrate, adjusting the pH of the aqueous solution to 7.6, and stirring uniformly to obtain a treated oxidized sodium hyaluronate aqueous solution;
[0097] (2) mixing the treated oxidized sodium hyaluronate aqueous solution with an activator, wherein the mass ratio of oxidized sodium hyaluronate to activator is 1:0.6, and mixing and stirring for 3 hours to obtain an activated oxidized sodium hyaluronate aqueous solution; the activator is N-(3-dimethylaminopropyl)-N-ethylcarbodiimide hydrochloride and adipic acid dihydrazide in a molar ratio of 1:5;
[0098] (3) The activated oxidized sodium hyaluronate aqueous solution was stirred and mixed with histidine and trehalose for 6 hours to obtain cross-linked oxidized sodium hyaluronate; the mass ratio of the oxidized sodium hyaluronate to histidine was 1:0.6, and the mass ratio of the oxidized sodium hyaluronate to trehalose was 1:0.1.
[0099] Example 6
[0100] The difference from Example 1 is that the molar ratio of the activator in step (2) is different. The activator in this comparative example is N-(3-dimethylaminopropyl)-N-ethylcarbodiimide hydrochloride and adipic acid dihydrazide in a molar ratio of 1:3.
[0101] The rest is the same as in Example 1.
[0102] Example 7
[0103] Different from Example 1, the histidine in step (3) is replaced by arginine.
[0104] The rest are the same as in Example 1.
[0105] Example 8
[0106] Different from Example 1, the oxidation degree of the oxidized sodium hyaluronate in step (1) is 20%, and the weight average molecular weight is 10 kDa.
[0108] The rest is the same as in Example 1.
[0109] Comparative Example 1
[0110] According to the technical solution in the Chinese invention patent with publication number CN104761734A, the cross-linked sodium hyaluronate gel is prepared as follows:
[0111] (1) A 4% (w / v) sodium hyaluronate aqueous solution (the weight average molecular weight of sodium hyaluronate is 36.8 kDa) is activated with acrylic acid. The pH of the filtrate after activation is 2.0.
[0112] (2) Tetrabutylammonium hydroxide (the molar ratio of hyaluronic acid to tetrabutylammonium hydroxide is 2:1) was added to the filtrate, stirred at room temperature for 2 h, and then freeze-dried.
[0113] (3) Take 2.5 g of freeze-dried hyaluronic acid sponge and dissolve it in 50 mL of dimethyl sulfoxide at a concentration of 5% (w / v), mix lysine ethyl ester dihydrochloride (the molar ratio of lysine ethyl ester dihydrochloride to hyaluronic acid is 1:2) and 2-chloro-1-methylpyridinium iodide (CMPI) (the molar ratio of CMPI to hyaluronic acid is 1:2), dissolve it in 2 mmL DMSO, add it dropwise to the reaction medium under stirring, add triethylamine (the molar ratio of triethylamine to hyaluronic acid is 1:1), and stir at room temperature overnight. First, dilute it with ice water, then dialyze it with water, NaOH, and NaCl respectively, and dialyze it with water again to the end point to obtain a cross-linked sodium hyaluronate gel.
[0114] Comparative Example 2
[0115] The difference from Example 1 is that the weight average molecular weight of the oxidized sodium hyaluronate raw material is 3 kDa. The rest is the same as Example 1.
[0116] This comparative example could not achieve crosslinking.
[0117] Comparative Example 3
[0118] Different from Example 1, the oxidation degree of the oxidized sodium hyaluronate raw material is 92% and the weight average molecular weight is 200 kDa.
[0119] The rest is the same as in Example 1.
[0120] Comparative Example 4
[0121] Different from Example 1, the activator in step (2) is only one component, N-(3-dimethylaminopropyl)-N-ethylcarbodiimide hydrochloride; the mass ratio of sodium hyaluronate to the activator is 1:0.5.
[0122] The rest is the same as in Example 1.
[0123] Comparative Example 5
[0124] The difference from Example 1 is that the arginine in step (3) is replaced by L-leucine.
[0125] The rest is the same as in Example 1.
[0126] Comparative Example 6
[0127] Different from Example 1, trehalose was not added in step (3).
[0128] The rest is the same as in Example 1.
[0129] Comparative Example 7
[0130] Different from Example 1, the reaction order of step (1) and step (2) is different, specifically:
[0131] (1) mixing oxidized sodium hyaluronate having an oxidation degree of 40% and a weight average molecular weight of about 36.8 kDa with water, wherein the solid-liquid ratio of oxidized sodium hyaluronate to water is 1:300 g / mL, to obtain an oxidized sodium hyaluronate aqueous solution; mixing the oxidized sodium hyaluronate aqueous solution with an activator, wherein the mass ratio of oxidized sodium hyaluronate to activator is 1:0.5, and mixing and stirring for 2 hours to obtain an activated oxidized sodium hyaluronate aqueous solution;
[0132] The activator is N-(3-dimethylaminopropyl)-N-ethylcarbodiimide hydrochloride and adipic acid dihydrazide in a molar ratio of 1:4;
[0133] (2) Adding sodium citrate to the activated oxidized sodium hyaluronate aqueous solution, adjusting the pH of the aqueous solution to 7.5, and stirring for 2 hours; then stirring and mixing with histidine and trehalose for 8 hours to obtain cross-linked oxidized sodium hyaluronate; the mass ratio of the oxidized sodium hyaluronate to histidine is 1:0.4, and the mass ratio of the oxidized sodium hyaluronate to trehalose is 1:0.2.
[0134] Test 1: Elasticity test
[0135] Cross-linked oxidized sodium hyaluronate was extruded to prepare a gel (a cylindrical sample with a diameter of 12 mm and a height of 5 mm), and its elastic modulus (Pa) was measured before and after being placed in an environment of 85° C. for 2 hours.
[0136] Testing method: At 25°C, a rotational rheometer was used to perform an oscillation test at a strain of 5%; the elastic modulus value (Pa) corresponding to a frequency of 1 Hz was taken for comparison.
[0137] The elastic modulus results of the cross-linked oxidized sodium hyaluronate of each embodiment and comparative example before and after being placed at 85° C. for 1 hour are shown in Table 1.
[0138] Elastic modulus loss (%) = (initial elastic modulus - elastic modulus after standing at 85°C for 1 hour) / initial elastic modulus × 100%.
[0139] Table 1
[0140] Initial elastic modulus (Pa) Elastic modulus after 1h at 85℃ (Pa) Elastic modulus loss, % Example 1 109.8 106.2 3.3 Example 2 107.1 102.3 4.5 Example 3 112.8 108.0 4.3 Example 4 106.5 101.3 4.9 Example 5 110.3 105.7 4.2 Example 6 103.9 100.2 3.6 Example 7 103.5 99.6 3.8 Example 8 93.4 89.9 3.7 Comparative Example 1 73.0 51.4 29.6 Comparative Example 3 144.2 138.4 4.0 Comparative Example 4 73.9 63.4 14.2 Comparative Example 5 50.1 34.2 31.6 Comparative Example 6 70.0 56.2 19.7 Comparative Example 7 71.8 61.0 15.0
[0141] Viscoelastic parameters can be used to evaluate whether sodium hyaluronate gelatin can maintain its intact structure and provide mechanical support in biological environments.
[0142] As can be seen from Table 1, the cross-linked oxidized sodium hyaluronate prepared by the preparation method of the present invention has a more stable internal structure, stronger properties, and higher support force. Moreover, the cross-linked oxidized sodium hyaluronate has a lower hardness, and when used as a dressing, it not only has a higher support force, but also can wrap the wound, promote anti-inflammation and wound healing. The cross-linked oxidized sodium hyaluronate of Comparative Example 3 feels harder.
[0143] In addition, the cross-linked oxidized sodium hyaluronate of the present invention has a small change in elastic modulus at 85° C. and has high stability. The cross-linked oxidized sodium hyaluronate of the comparative example has a weak cross-linking strength, and its molecular chain is easily broken under high temperature conditions, and its hydration is reduced, and its elasticity and viscosity are significantly reduced, and its stability is weak.
[0144] Test 2 Toxicology test
[0145] The prepared cross-linked oxidized sodium hyaluronate was subjected to skin irritation test, in vitro cytotoxicity test and skin sensitization test respectively.
[0146] 1. Skin irritation test
[0147] Reference standards:
[0148] GB / T 16886.10-2017 Biological evaluation of medical devices Part 10: Irritation and skin sensitization tests; GB / T16886.12-2017 Biological evaluation of medical devices Part 12: Sample preparation and reference materials.
[0149] Test substance: cross-linked oxidized sodium hyaluronate obtained in each example and comparative example.
[0150] Positive control: 10% sodium dodecyl sulfate aqueous solution, the solvent is deionized water.
[0151] The skin reaction scoring criteria are shown in Table 2.
[0152] Table 2
[0153]
[0154] Under the technical conditions of the present invention, the primary irritation score and cumulative irritation index of the prepared cross-linked oxidized sodium hyaluronate were both 0, and no erythema or edema was observed. The primary irritation score of the positive control was 2.67.
[0155] 2. In vitro cytotoxicity test
[0156] Reference standards:
[0157] GB / T 16886.5-2017 Biological evaluation of medical devices Part 5: In vitro cytotoxicity tests; GB / T16886.12-2017 Biological evaluation of medical devices Part 12: Sample preparation and reference materials.
[0158] Test substance: cross-linked oxidized sodium hyaluronate obtained in each example and comparative example.
[0159] Negative control (high-density polyethylene): Carefully place high-density polyethylene on the cell layer in the center of each vessel, ensuring that the sample covers about one-tenth of the cell layer surface, and culture for 24 hours (37±1°C).
[0160] Positive control (10% DMSO): DMSO was carefully placed on the cell layer in the center of each dish, ensuring that the sample covered about one tenth of the cell layer surface, and cultured for 24 h (37±1° C.).
[0161] Experimental steps: Enzymatic digestion (trypsin) Remove the cultured cells from the culture flask and centrifuge the cell suspension at 200g for 3 minutes. Resuspend the cell suspension in culture medium and adjust the density to 1×10 5 100 μL of culture medium was added to the outer wells of a 96-well tissue culture microtiter plate, and 100 μL of a 1×10 5 Cell suspension of 10 cells / mL. Incubate the cells for 24 hours (5% CO2, 37°C, >90% humidity) to form a semi-confluent monolayer. Aspirate the culture medium and add the sample, negative control, positive control or blank control treatment medium to each well. Incubate the cells for 24 hours (5% CO2, 37°C, >90% humidity). Check each plate under a microscope to determine the cell seeding system error and the growth characteristics of the control and test group cells. After the plate inspection, carefully remove the culture medium, add 50μL MTT (1mg / mL) solution to each well, incubate in a 37°C incubator for another 2 hours, discard the MTT solution, add 100μL isopropanol solution to each well, shake the plate, and measure the absorbance at 570nm with a microplate reader.
[0162] Cell survival rate (%) = 100 × OD570 e / OD570 b , among which OD570 eThe average optical density of the test sample 100% sample solution; OD570 b is the average optical density of the blank.
[0163] Judgment basis: If the cell viability drops to <70% of the blank, it has potential cytotoxicity.
[0164] The results of the cytotoxicity test were as follows: the cell survival rate of the negative control was 98.1%, the cell survival rate of the positive control was 12.3%, the cell survival rate of the cross-linked oxidized sodium hyaluronate in the example was 78.4%-93%, and the cell survival rate of the cross-linked oxidized sodium hyaluronate in the comparative example was 71%-80.3%.
[0165] According to GB / T 16886.5-2017, under the experimental conditions, the cross-linked oxidized sodium hyaluronate of the present invention has no potential cytotoxicity to L929 mouse fibroblasts.
[0166] 3. Skin sensitization test
[0167] Reference standards:
[0168] GB / T 16886.10-2017 Biological evaluation of medical devices Part 10: Irritation and skin sensitization tests; GB / T16886.12-2017 Biological evaluation of medical devices Part 12: Sample preparation and reference materials.
[0169] Test substance: cross-linked oxidized sodium hyaluronate obtained in each example and comparative example.
[0170] Positive control: 2,4-dinitrochlorobenzene solution (solvent: 80% ethanol) with induction and stimulation concentrations of 0.2% and 0.1%, respectively.
[0171] The grading standards are shown in Table 3.
[0172] Table 3
[0173] Patch test reaction grade No significant change 0 Sporadic or macular erythema 1 Moderate confluent erythema 2 Severe erythema and edema 3
[0174] The test results showed that all animals in the positive control group had allergic reactions, indicating that the test animals were sensitive and the test was reliable. The skin sensitization reaction of animals in the cross-linked oxidized sodium hyaluronate group was grade 0, the fatality rate was 0%, and no skin sensitization reaction was induced.
[0175] Experiment 3: Wound healing promotion test
[0176] The cross-linked oxidized sodium hyaluronate of the embodiment and comparative example was taken and relevant animal test was carried out according to the following skin wound repair test protocol.
[0177] Establishment of mouse skin wound model: The mice were anesthetized with ether, and the hair on the back was clipped. The hair on the back was shaved with a razor, and the skin was cleaned and disinfected with 70% ethanol. A circular mark slightly larger than 1 cm in diameter was made at the same position on both sides of the spine. A full-thickness skin wound was made in the circular mark with a 1 cm diameter skin biopsy punch under sterile conditions. After modeling, the wound was exposed and the mice were kept in a single cage. The day of injury was recorded as day 0.
[0178] Experimental animal grouping: SPF grade 18-22g male Kunming mice, after 1 week of adaptive feeding, were randomly divided into 14 groups, 8 in each group, including Example 1-Example 8 groups, Comparative Example 1 group, and Comparative Example 3-Comparative Example 7 groups. The corresponding cross-linked oxidized sodium hyaluronate samples (sterilized by ultraviolet irradiation before use) were used to treat mouse skin wounds. The wound healing was observed within 14 days. On the last day, blood was collected from the orbital venous plexus of each group of mice, and the EILSA kit was used to detect the content of mouse serum inflammatory factor IL-1β.
[0179] Mouse skin wound healing rate (%) = (original wound area - unhealed wound area) / original wound area × 100%.
[0180] Wound healing (complete epithelialization of wound surface) standard: Complete healing occurs when the healing area is greater than 95% of the original wound area, or the wound area is less than 5% of the original wound area.
[0181] The results of wound healing rate and inflammatory factor IL-1β content are shown in Table 4.
[0182] Table 4
[0183]
[0184] In Table 4, each comparative example group is compared with the example 1 group. # P≤0.05, ## P≤0.01, there is a significant difference.
[0185] As can be seen from Table 4, the cross-linked oxidized sodium hyaluronate in the example group significantly improved the wound healing rate of mice within one week, while the wound healing rate of the cross-linked oxidized sodium hyaluronate in the comparative example group was lower within 14 days; a large amount of organic solvent was used in the preparation process of the cross-linked sodium hyaluronate gel in comparative example 1, and the gel product had more or less organic solvent residue, which was not conducive to wound healing; the mice in comparative example 3 were prone to scratching, which was not conducive to wound healing; the cross-linked oxidized sodium hyaluronate in comparative example 4 had low elasticity and viscosity, low supporting force, and was not conducive to wound healing.
[0186] In addition, the cross-linked oxidized sodium hyaluronate in the example group has a significant anti-inflammatory effect and a significant effect of reducing the content of inflammatory factors.
[0187] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing cross-linked oxidized sodium hyaluronate, characterized in that: Includes steps: (1) mixing oxidized sodium hyaluronate with water, adding sodium citrate to adjust the pH to 7.0-8.0, and obtaining a treated oxidized sodium hyaluronate aqueous solution; the oxidized sodium hyaluronate has an oxidation degree of 10%-90% and a weight average molecular weight of 5 kDa-200 kDa; (2) mixing the oxidized sodium hyaluronate aqueous solution treated in step (1) with an activator to obtain an activated oxidized sodium hyaluronate aqueous solution; the activator is a mixture of adipic acid dihydrazide and carbodiimide; (3) cross-linking the activated oxidized sodium hyaluronate aqueous solution in step (2) with amino acids and trehalose to obtain cross-linked oxidized sodium hyaluronate; The amino acid is selected from at least one of histidine, arginine, ε-polylysine or its hydrochloride, glutamine and asparagine.
2. The preparation method according to claim 1, characterized in that: In step (1), the degree of oxidation of the oxidized sodium hyaluronate is 20%-75%.
3. The preparation method according to claim 2, characterized in that: In step (1), the degree of oxidation of the oxidized sodium hyaluronate is 20%-50%.
4. The preparation method according to claim 3, characterized in that: In step (1), the degree of oxidation of the oxidized sodium hyaluronate is 25%-45%.
5. The preparation method according to claim 1, characterized in that: In step (1), the weight average molecular weight of the oxidized sodium hyaluronate is 10 kDa-100 kDa.
6. The preparation method according to claim 5, characterized in that: In step (1), the weight average molecular weight of the oxidized sodium hyaluronate is 10 kDa-50 kDa.
7. The preparation method according to claim 6, characterized in that: In step (1), the weight average molecular weight of the oxidized sodium hyaluronate is 25 kDa-50 kDa.
8. The preparation method according to claim 7, characterized in that: In step (1), the weight average molecular weight of the oxidized sodium hyaluronate is 30 kDa-45 kDa.
9. The preparation method according to claim 1, characterized in that: In step (1), the solid-liquid ratio of the oxidized sodium hyaluronate to water is 1:250-400 g / mL; and the pH is 7.2-7.
6.
10. The preparation method according to claim 1, characterized in that: In step (2), the molar ratio of adipic acid dihydrazide to carbodiimide is 1:3-5; the mass ratio of oxidized sodium hyaluronate to activator is 1:0.3-0.6; and the mixing reaction time is 0.5-3h.
11. The preparation method according to claim 10, characterized in that: In step (2), the molar ratio of adipic acid dihydrazide to carbodiimide is 1:3-4; the mass ratio of oxidized sodium hyaluronate to activator is 1:0.5; and the mixing reaction time is 1-2h.
12. The preparation method according to claim 1, characterized in that: In step (3), the mass ratio of oxidized sodium hyaluronate to amino acid is 1:0.1-1; the mass ratio of oxidized sodium hyaluronate to trehalose is 1:0.05-0.5; and the reaction time is 4-12h.
13. The preparation method according to claim 12, characterized in that: In step (3), the mass ratio of the oxidized sodium hyaluronate to the amino acid is 1:0.2-0.6; the mass ratio of the oxidized sodium hyaluronate to trehalose is 1:0.1-0.3; and the reaction time is 6-10 hours.
14. The cross-linked oxidized sodium hyaluronate prepared by the preparation method according to any one of claims 1 to 13, characterized in that: The preparation raw materials include: oxidized sodium hyaluronate, sodium citrate, adipic acid dihydrazide, carbodiimide, amino acid and trehalose; The oxidation degree of the oxidized sodium hyaluronate is 10%-90%, and the weight average molecular weight is 5kDa-200kDa; The amino acid is selected from at least one of histidine, arginine, ε-polylysine or its hydrochloride, glutamine and asparagine.
15. The cross-linked oxidized sodium hyaluronate according to claim 14, characterized in that: The molar ratio of adipic acid dihydrazide to carbodiimide is 1:3-5; the mass ratio of oxidized sodium hyaluronate to activator is 1:0.3-0.6; The mass ratio of the oxidized sodium hyaluronate to the amino acid is 1:0.1-1; The mass ratio of the oxidized sodium hyaluronate to trehalose is 1:0.05-0.
5.
16. Use of cross-linked oxidized sodium hyaluronate in the preparation of a drug with high stability, wound healing promotion, anti-inflammatory and antioxidant effects, characterized in that: The cross-linked oxidized sodium hyaluronate is the cross-linked oxidized sodium hyaluronate prepared by the preparation method according to any one of claims 1 to 13, or the cross-linked oxidized sodium hyaluronate according to any one of claims 14 to 15.
17. A use of cross-linked oxidized sodium hyaluronate in the preparation of cosmetics with high stability, wound healing promotion, anti-inflammatory and antioxidant effects, characterized in that: The cross-linked oxidized sodium hyaluronate is the cross-linked oxidized sodium hyaluronate prepared by the preparation method according to any one of claims 1 to 13, or the cross-linked oxidized sodium hyaluronate according to any one of claims 14 to 15.
Citation Information
Patent Citations
Preparation method of amino acid crosslinked sodium hyaluronate gel
CN104761734A
Injectable hydrogel, preparation method and application of injectable hydrogel and joint lubricant
CN111228579A
Adhesive healing-promoting hemostatic sponge and preparation method thereof
CN112007202A
Sodium hyaluronate gel as well as preparation method and application thereof
CN114404355A
Cited By
Lidocaine hydrochloride-containing sodium hyaluronate gel for injection and preparation method of lidocaine hydrochloride-containing sodium hyaluronate gel
CN121668097A